2022
DOI: 10.1371/journal.pone.0262208
|View full text |Cite
|
Sign up to set email alerts
|

Younger generations are more interested than older generations in having non-domesticated animals as pets

Abstract: The trade and private ownership of non-domesticated animals has detrimental effects on individual animals and their wild populations. Therefore, there is a need to understand the conditions that motivate and dissuade interest in non-domesticated pet ownership. Past research has demonstrated that the way in which non-domesticated animals are portrayed in images influences the public’s perception that they are suitable as pets. We conducted an online survey of people residing in the United States to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…People may be particularly drawn to nonhuman primates, our closest evolutionary relatives (Barash, 2014). A few recent studies have failed to find an increase in pet interest when nonprimate species are shown in close proximity to people (Cronin et al., 2022; Spooner & Stride, 2021); however, more work is needed to gain confidence that these null results represent a true lack of risk (Alba et al., 2023; Cronin et al., 2022). We hypothesize our findings will extend to some other groups of wildlife and recommend further research into social media portrayals for their effects on pet interest and perceptions of wildlife conservation, particularly with regard to images of charismatic and oft‐traded megafauna, such as big cats (United Nations Office on Drugs & Crime, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…People may be particularly drawn to nonhuman primates, our closest evolutionary relatives (Barash, 2014). A few recent studies have failed to find an increase in pet interest when nonprimate species are shown in close proximity to people (Cronin et al., 2022; Spooner & Stride, 2021); however, more work is needed to gain confidence that these null results represent a true lack of risk (Alba et al., 2023; Cronin et al., 2022). We hypothesize our findings will extend to some other groups of wildlife and recommend further research into social media portrayals for their effects on pet interest and perceptions of wildlife conservation, particularly with regard to images of charismatic and oft‐traded megafauna, such as big cats (United Nations Office on Drugs & Crime, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on nonhuman primates have shown that images of primates in humanized settings can lead to a misunderstanding of the status of these animals in the wild and increase the appeal of some species as pets (Leighty et al, 2015;Kitson and Nekaris, 2017;Freund et al, 2021). Recently, studies of other species, such as felids, snakes, parrots, kangaroos, insects, and sloths, have been published with less clear conclusions (van der Meer et al, 2019;Shaw et al, 2021;Spooner and Stride, 2021;Cronin et al, 2022;Alba et al, 2023). Some authors consistently report that more research is needed in this area (van der Meer et al, 2019;Otsuka and Yamakoshi, 2020;Thomas-Walters et al, 2020;Shaw et al, 2021;Alba et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions explain the complexity of interpreting perceptions of wildlife images (Thomas-Walters et al, 2020;Shaw et al, 2021), especially based on a single, short-term viewing. Several researchers have pointed out the need to consider cumulative impacts of viewing (Cronin et al, 2022) as well as attitudes and behavioral consequences over time (Alba et al, 2023;van der Meer et al, 2019). Wildlife rehabilitators often use behavioral change methods to encourage action among members of the public who already care about wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to domestic animals, wildlife such as primates, reptiles, and protected wild birds are becoming preferred as pets (Nijman 2009;Chng et al 2015;Morgan and Chng 2018). Based on previous research in the United States, the media is influential in portraying wildlife not commonly kept as pets to be accompanied at home (Leighty et al 2015;Cronin et al 2022). The younger the respondent, the higher the interest in keeping exotic animals.…”
Section: Introductionmentioning
confidence: 99%
“…The younger the respondent, the higher the interest in keeping exotic animals. On the other hand, gender plays a significant role in how to keep exotic animals, reptiles such as snakes, but not significantly in keeping mammals such as sloths (Cronin et al 2022).…”
Section: Introductionmentioning
confidence: 99%